HUBUNGAN HASIL AKURASI SMASH FOREHAND PADA BULU TANGKIS PB DAREK - Burhan, Zakir; Hidayat, Taufiq; Herlina, Herlina (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The purpose of this research is to determine the relationship between wrist flexibility and badminton forehand smash accuracy, to determine arm length and badminton forehand smash accuracy, to determine body height and badminton forehand smash accuracy, to find out the relationship between wrist flexibility, arm length and body height. Badminton Forehand Smash Accuracy. This research uses quantitative descriptive methods with a correlational approach, the population in this research are all athletes who take part in the PB Darek badminton club, the sample in this research is 17 athletes. The sampling technique uses total sampling. The results of this research can be seen that the magnitude of the relationship between wrist flexibility (X1) with Badminton Forehand Smash Accuracy of 68.72%. And the variable arm length (X2) gives a relationship of 57.15%. The variable Body Height (X3) gives a relationship of 55.80%. and the magnitude of the relationship between Wrist Flexibility, Arm Length and Body Height together with Badminton Forehand Smash Accuracy is 63.04%.